2009
DOI: 10.1016/j.clp.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Effects of Psychoactive Drugs

Abstract: There has been a longstanding concern with the fetal effects of psychoactive drug use by pregnant women. In this article we describe the effects of three drugs with similar molecular targets that involve monoaminergic transmitter systems. These stimulants include the illegal drugs cocaine and methamphetamine and the class of selective serotonin re-uptake inhibitors (SSRIs) used to treat maternal depression during pregnancy. We discuss the mechanisms of action of each drug, including a possible common epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
65
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 173 publications
(152 reference statements)
4
65
0
2
Order By: Relevance
“…Last, PME causes a downregulation of the placental norepinephrine transporter and 11β-hydroxysteroid dehydrogenase-2, which protect the fetus against the excess catecholamines and glucocorticoids. Consequent cortisol overexposure can adversely affect the programming of the HPA axis (Salisbury et al, 2009). Therefore, the observed increased cortisol reactivity to a stressful task among children in this study is in line with the suggested effects PME has on the fetus's HPA-axis programming.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Last, PME causes a downregulation of the placental norepinephrine transporter and 11β-hydroxysteroid dehydrogenase-2, which protect the fetus against the excess catecholamines and glucocorticoids. Consequent cortisol overexposure can adversely affect the programming of the HPA axis (Salisbury et al, 2009). Therefore, the observed increased cortisol reactivity to a stressful task among children in this study is in line with the suggested effects PME has on the fetus's HPA-axis programming.…”
Section: Discussionsupporting
confidence: 72%
“…The fi ndings fi rst support the hypothesis that PME may relate to alterations in the function of the HPA axis (Salisbury et al, 2009). Because methamphetamine is a stimulant of the sympathetic nervous system, prenatal exposure can cause increased synaptic concentrations of dopamine, serotonin, and norepinephrine.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations